G=4(x+9)-(7+x)(x+1)

Simple and best practice solution for G=4(x+9)-(7+x)(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for G=4(x+9)-(7+x)(x+1) equation:


Simplifying
G = 4(x + 9) + -1(7 + x)(x + 1)

Reorder the terms:
G = 4(9 + x) + -1(7 + x)(x + 1)
G = (9 * 4 + x * 4) + -1(7 + x)(x + 1)
G = (36 + 4x) + -1(7 + x)(x + 1)

Reorder the terms:
G = 36 + 4x + -1(7 + x)(1 + x)

Multiply (7 + x) * (1 + x)
G = 36 + 4x + -1(7(1 + x) + x(1 + x))
G = 36 + 4x + -1((1 * 7 + x * 7) + x(1 + x))
G = 36 + 4x + -1((7 + 7x) + x(1 + x))
G = 36 + 4x + -1(7 + 7x + (1 * x + x * x))
G = 36 + 4x + -1(7 + 7x + (1x + x2))

Combine like terms: 7x + 1x = 8x
G = 36 + 4x + -1(7 + 8x + x2)
G = 36 + 4x + (7 * -1 + 8x * -1 + x2 * -1)
G = 36 + 4x + (-7 + -8x + -1x2)

Reorder the terms:
G = 36 + -7 + 4x + -8x + -1x2

Combine like terms: 36 + -7 = 29
G = 29 + 4x + -8x + -1x2

Combine like terms: 4x + -8x = -4x
G = 29 + -4x + -1x2

Solving
G = 29 + -4x + -1x2

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Simplifying
G = 29 + -4x + -1x2

See similar equations:

| (4b^3+9b^2-6)+(3b^3-9b+8)= | | Y+9=-2 | | 8(6x-1)=6x+1 | | -(6y+1)-(5y-8)=1 | | -79-10x=7*23 | | u-3u=10+8 | | y=-11+6x | | 8+5m-1=9m+11-3 | | 8v=-7 | | 3(x+2)+2(3x+2)=28 | | 2(4-2x+x^2)-x(x+2)= | | 33x-10-17x=4(4x-3)+2 | | 1+3n-5n=12 | | 6r-4r=16 | | 8x+14x=132 | | 16x^2+38x-5=0 | | (3x+5)-(-7x+8)= | | 2y-3x=0 | | 5(3+6x)-5=70 | | -7g=49 | | 4(4x+2)=20-2(x-3) | | x^4-81-x^3+9=0 | | -7(3-x+3)=-18 | | 58q-2.8-5.2q=-0.4-2.2 | | 2x^2-24x+81=0 | | 14x^2+40x-6=0 | | x-7.6=-6.5 | | 12=-24y | | 4x+40=13x-68 | | r+33=14 | | -2t^2-6t+5=0 | | 5y-2+y+48=5y+50-1y |

Equations solver categories